2015
DOI: 10.1002/pon.3901
|View full text |Cite
|
Sign up to set email alerts
|

Cancer patient autonomy and quality of dying-a prospective nationwide survey in Taiwan

Abstract: We concluded that physician-assessed autonomy would affect a good death and was highly correlated with age, consciousness level, and quality of dying at the end for advanced cancer patients in Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
(35 reference statements)
1
11
0
2
Order By: Relevance
“…This hypothesis is based on the empirical finding that these interventions were associated with a higher QODD in patients with cancer. [16][17][18][19] We divided patients with ILD into three groups based on the presence or absence of palliative care access (ie, specialised palliative care services, opioid use or both) and their participation in end-oflife discussions: patients without both palliative care access and participation in end-of-life discussion (group A); patients with either palliative care access or participation in end-of-life discussion (group B); and patients with both palliative care access and participation in end-of-life discussion (group C). Each group was ranked according to the intensity of the interventions, and the Jonckheere-Terpstra trend test was performed to explore the associations between these interventions and GDI score.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is based on the empirical finding that these interventions were associated with a higher QODD in patients with cancer. [16][17][18][19] We divided patients with ILD into three groups based on the presence or absence of palliative care access (ie, specialised palliative care services, opioid use or both) and their participation in end-oflife discussions: patients without both palliative care access and participation in end-of-life discussion (group A); patients with either palliative care access or participation in end-of-life discussion (group B); and patients with both palliative care access and participation in end-of-life discussion (group C). Each group was ranked according to the intensity of the interventions, and the Jonckheere-Terpstra trend test was performed to explore the associations between these interventions and GDI score.…”
Section: Discussionmentioning
confidence: 99%
“…By using the validated 'Good Death Scale' we had previously developed, we measured the associated correlates that affect quality of dying and patient autonomy. Four medical centers participated in the study and the team held monthly teleconference discussions (5).…”
Section: Taiwan Research Network and Cross-cultural Collaborationmentioning
confidence: 99%
“…The use of aggressive medical treatments for cancer patients aware of their prognosis in the last month of life, such as CPR and intubation, also declined over this period. In addition, research concluded that physician-assessed autonomy is an important factor allowing for a good death, and is highly correlated with age, level of consciousness and quality of dying at the end of life in advanced cancer patients in Taiwan (5). Community engagement, in particular to help the patient and family achieve a good death at home, has been progressing, due to the cultural propensity to die at home (6).…”
Section: Introductionmentioning
confidence: 99%
“…O esforço contínuo da equipe de CP em preservar a autonomia do paciente aumenta a qualidade do morrer, já que um paciente consciente da iminência da morte pode contribuir com o plano de tratamento e facilitar o processo de aceitação da terminalidade da vida, da propriedade em realizar seus desejos e da pontualidade em escolher o momento adequado para tal (CHENG et al, 2016). Esta categoria apresenta os conhecimentos adquiridos durante a formação acadêmica dos profissionais de saúde envolvidos nos cuidados com a criança.…”
Section: ) Compreensão E Desenvolvimento Dos Cuidados Paliativosunclassified